Visual Analysis of Two‐Phase Flow Displacement Processes in Porous Media. (6th December 2021) - Frey, Steffen; Scheller, Stefan; Karadimitriou, Nikolaos; Lee, Dongwon; Reina, Guido; Steeb, Holger; Ertl, Thomas
Abstract: We developed a new visualization approach to gain a better understanding of the displacement of one fluid phase by another in porous media. This is based on a recent experimental parameter study with varying capillary numbers and viscosity ratios. We analyse the temporal evolution of characteristic values in this two‐phase flow scenario and discuss how to directly compare experiments across different temporal scales. To enable spatio‐temporal analysis, we introduce a new abstract visual representation showing which paths through the porous medium were occupied and for how long. These transport networks allow to assess the impact of different acting forces and they are designed to yield expressive comparability and linking to the experimental parameter space both supported by additional visual cues. This joint work of porous media experts and visualization researchers yields new insights regarding two‐phase flow on the microscale, and our visualization approach contributes towards the overarching goal of the domain scientists to characterize porous media flow based on capillary numbers and viscosity ratios. Abstract : We developed a new visualization approach to gain a better understanding of the displacement of one fluid phase by another in porous media.